Case report on a huge paraovarian cyst - N Asnafi; Sh Shafai; M Sharbatdaran (JRI, 2004)
Introduction: Paraovarian cysts originate from peritoneum, tube or Wolfian ducts. They are usually very small and their maximum diameter is two centimeters, most often discovered accide-ntttally during the operation. In sonographic view, they have the same characteristics as ovarian cysts, being differentiated by smaller size, adjacency to ovary and persistence. Rupture, hemorrh-age and torsion of paraovarian cysts occasionally occur, but their voluminous enlargement rarely happens. The aim of the present case report is introduction of the probability, diagnosis and treat-ment of huge paraovarian cysts. Case Report: The patient was a 48 years old woman with history of four cesarean deliveries and no abortions (G4P4Ab0), referred to Gynecology Clinic of Shahid Yahya Nejad Hospital, Babol, complaining about abdominal distension and vaginal bleeding. In physical examination, a distend-ed abdomen with a soft tumor extended form pelvis to over umbilicus was palpable. Laparotomy was planned using sonographic diagnosis of pelvic mass. The uterine size was found to be larger than normal (1109481mm) during the operation. The right ovary was normal but the left ovary contained a small 3cm cyst. A huge cystic mass, originating form lateral side of the right ovary, filled the whole abdominal cavity up to the diaphragm. A sample of 20ml of the cystic fluid was first aspirated with syringe and sent for cytological study. Then 2800 ml fluid from the cyst was evacuated. Finally, cystectomy and total hysterectomy with bilateral salpingo-oophorectomy was performed. The pathology report was paraovarian cyst. Conclusion: According to many reports, when a sonographic study shows the ovaries close to a pelvic cyst, paraovarian cyst is one of the first diagnostic choices and accordingly the treatment plan could be selected with a cyst aspiration followed by laparoscopic cystectomy or laparotomy.
Keywords: Paraovarian cyst, Pelvic cyst, Abdominal distention, Ovarian cyst